Using simultaneous counts by independent observers to correct for observer variability and missed sightings in a shore-based survey of bottlenose dolphins, Tursiops truncatus - F. YOUNG , ROBERT; PEACE, SALLY (J. Cetacean Res. Manage., 1999)
Simultaneous counts by independent shore-based observers have been used to generate revised population estimates for gray and bowhead whales, but no similar technique has been applied to shore-based dolphin surveys. Shore-based whale surveys generally rely on a single observation site from which migrating whales are counted as they pass in one direction over a period of weeks to months. Shore-based dolphin surveys, however, typically use multiple observation sites over a much shorter time period (hours) in order to avoid double counting individuals as they change direction. This paper reports on a new technique to correct for observer variability and missed sightings for coastal bottlenose dolphin surveys conducted at Myrtle Beach, South Carolina, USA. Comparisons were made between concurrent counts by 39 pairs of independent shore-based observer teams. A model was developed to revise observer estimates in which the number of observed dolphin groups was multiplied by a correction factor to estimate the true number of groups, and this number in tum was multiplied by the mean group size to determine the total number of dolphins. The true number of dolphin groups was estimated using a modified Petersen mark-recapture estimate, stratified by group-size category. The mean proportion of groups missed by observers was negatively correlated with reported group size: 32.7% for groups of 1-2 dolphins; 16.5% for groups of 3-4 dolphins; and 9.9% for groups of >4 dolphins. A variability factor was also calculated to determine a confidence interval for the average number of dolphins per group, based on the mean percent difference between paired observer teams, stratified by group size. The model was used to calculate revised estimates for shore-based bottlenose dolphin surveys conducted in South Carolina in 1994 and 1995. The original uncorrected abundance estimates were increased by a factor of 1.14 and 1.19 respectively, comparable to similar calculations from shore-based surveys of gray whales. However, the estimated confidence interval of± 38% of the revised estimates is approximately four times the magnitude found in the gray whale studies. This difference is primarily due to the large observer variability for estimated dolphin group size and can be reduced using various revisions of survey design and methodology. Ideal conditions for this technique include elevated observer posts and accurate estimates of the proportion of the population within visual range of the coastline. This study demonstrates that shore-based dolphin surveys are a potentially efficient census technique and an attractive low cost alternative to aerial and boat surveys.